Methods for Strategizing Sustainable Development of Poland - Isaieva Nataliya I.; Degtiarova Olga V. (Problemi Ekonomiki, 2018)
The aim of the article is to study the methods for strategizing sustainable development of Poland. The article analyzes the experience, legislative, and methodological support of the strategizing of Poland. A logical scheme is developed for determining and approving the strategic goals and development priorities of the Polish strategies. The general structure is built, and the content of the Development Strategy is determined. It is established that the assessment of the relevance, realization, and influence of the Strategy on the implementation of the strategic goals is a mandatory element in the process of working out the Development Strategy. The relevance of the implementation is substantiated, and the use of Poland’s practice of strategizing in the process of reforming Ukraine’s strategic planning system is proposed.